Digital Governance and Public Sector Innovation in Somalia: Enhancing Transparency, Efficiency, and Citizen Participation through Technology - Hashi, Abdinasir Ismael (European Journal of Information and Knowledge Management, 2025)
Purpose: This study investigates the transformative role of digital governance in Somalia’s public sector, with a focus on how digital solutions can enhance transparency, operational efficiency, and citizen participation. Methodology: To achieve this, the study develops a novel hybrid framework known as the SyMAP-Tech (Systematic Mapping and Participatory Technology Assessment) Framework. This approach combines systematic literature mapping with participatory technology assessment, enabling a comprehensive evaluation of the readiness, applicability, and impact of digital tools within fragile governance systems. Stakeholder engagement was central to this process, with localized digital platforms and citizen feedback mechanisms used to generate real-time input. In total, 116 digital participation tools, adapted from international best practices, were reviewed and mapped to Somalia’s governance ecosystem. Findings: The results reveal significant potential for digital solutions to bridge gaps in public accountability and service delivery, particularly in urban areas where infrastructure is relatively more developed. The analysis also identifies clusters of tools that are particularly effective in promoting inclusive policymaking, ensuring transparent procurement, and strengthening citizen oversight. Furthermore, the study highlights the importance of localized strategies that integrate both policy analysis and direct stakeholder participation to build legitimacy and trust in governance systems. Unique Contribution to Theory, Practice, and Policy: The research makes several contributions. At the theoretical level, it introduces the SyMAP-Tech Framework as a replicable model for evaluating digital governance within fragile and post-conflict states. In practice, it offers Somali institutions actionable insights into how digital solutions can be harnessed to improve service delivery, strengthen accountability, and enhance citizen engagement. For policy, the study recommends the adoption of context-driven digital governance strategies that are tailored to fragile state-building, with particular emphasis on transparency, trust-building, and institutional resilience.